Investigation of the effects of various defects in metallic specimens on the spatial distribution of pulsed eddy currents - Sophian, Ali; Nafiah, Faris (2018)
attention from researchers around the globe. Thanks to its richness of spectral components, various applications of this technique have been proposed and reported in the literature covering both structural integrity inspection and material characterization in various industrial sectors. In this project it was hypotesized that the spatial and temporal magnetic field signals can offer more information of the defects compared to single point data, which have been proven in this project, through numerical modelling and analysis of experimental data gathered by using a PEC system developed in the project. In this project, it has been shown that there is some unique correlation between the spatial distribution of the eddy current and the characteristics of defetcs, including their sizes. In this project, particulary this was studied by using normal and inclined cracks that are located on both surface and sub-surface. This finding can be utilized to enrich even further the information that we can extract from PEC signals.